The role of policy champions and learning in implementing horizontal environmental policy integration: Comparative insights from European structural fund programmes in the U.K. - Tony Gore (Administrative Sciences, 2014)
This paper examines attempts to integrate environmental sustainability goals into the design and implementation of projects funded by the EU Structural Funds programmes in the U.K. between 2000 and 2006. It does so by comparing how the two "horizontal priorities" (environmental sustainability and gender equality) fared in terms of understanding and acceptance by project applicants. It places this material within the wider context of literature on environmental policy integration and inter-agency cooperation. A "policy coordination" framework is used as a heuristic device to construct an account of the ways in which the two themes were handled through the interplay of the myriad of actors and organisations involved in the process. A key part in this involved the deployment of "policy champions" to work with external organisations bidding for funding to support projects that formed the core of programme implementation. The paper also examines the variable reactions on the part of project designers to the requirement to incorporate environmental and gender goals and the greater inter-professional networking that these implied. The comparison between the two priorities clearly demonstrates the difficulties inherent in the breadth and complexity of environmental issues and the need in the first instance to link them to relatively simple actions directly associated with economic development activity. The study concludes that this is essentially the first step in a more protracted "policy learning" process.
Keywords: 350; policy coordination; policy champions; environmental policy integration; European Structural Funds; horizontal priorities